A construção processual da santidade: abordagem e interpretação da causa de Antônio Galvão de França - Souza, Leandro Faria de (2018)
The Holiness is present in the history of the Catholic Church from its earliest days, when the early followers of Christ sought to imitate it through martyrdom. Gradually, the representation of this concept has changed, gaining political elements elaborated by the Church as a form of control and deepening of the institutional relations with each locality. In this sense, the process of canonization of Antônio Galvão de França represents an important landmark for the introduction of Brazil into the universal Catholic scenario. Therefore, the main objective of this work is to analyze the act of beatification and canonization of the first Brazilian saint as a historical process and through him to identify, through his heroic virtues described in the document (canonization process), a new possible approach for this documentation and, at the same time, demonstrate the occurrence of a process of symbolic construction of the memory of sanctity, which involved social groups interested in its promotion to the status of saint, enabling the success of this canonization to promote the "procedural construction of holiness"